Review on corrosion performance of laser powder-bed fusion printed 316L stainless steel: Effect of processing parameters, manufacturing defects, post-processing, feedstock, and microstructure - V.B. Vukkum; R.K. Gupta (Materials & Design, 2022)
The applications of laser-powder bed fusion (LPBF), an emerging additive manufacturing (AM) technique, are rapidly growing in various industries. The superior and consistent mechanical and corrosion properties of LPBF-printed components are essential for engineering applications. The 316L stainless steel (SS) is an essential alloy with widespread applications from household items to nuclear and aerospace industries. Extensive research is conducted to understand and improve the mechanical properties of LPBF printed 316L SS. Studying the corrosion behavior of LPBF printed 316L has attracted only limited attention. Additionally, a discrepancy in the corrosion performance of LPBF printed 316L has been reported due to the complex microstructure and defects introduced during LPBF. Therefore, understanding the influence of processing parameters and feedstock on defects and microstructure becomes critical in understanding the processing-corrosion relationships and producing LPBF printed 316L components with reproducible properties. This review presents the influence of feedstock, processing parameters, and post-processing techniques on manufacturing defects, microstructure, and corrosion performance of LPBF printed 316L. Strategies and hypotheses to improve the corrosion resistance of LPBF printed 316L are also presented.